Enzymatic ethanolysis of high free fatty acid jatropha oil using Eversa Transform. (9th February 2022) - Bouaid, Abderrahim; Acherki, Hassan; Bonilla, Marcos Herguedas; Marchetti, Jorge Mario
Abstract : A reduction of the cost of enzymatic biodiesel is crucial to make it competitive with known technologies. A single-step process for the conversion of high free fatty acid oils into fatty acid ethyl esters using a low-cost lipase was developed. Abstract : The reduction of the cost of enzymatic biodiesel is crucial to make it competitive with more well-known and settle technologies; therefore, there is a need for a single-step process for the conversion of high free fatty acid oils into fatty acid ethyl esters (FAEEs) using a low-cost lipase. Jatropha oil, with high free fatty acid (FFA) content (9.4%), was transformed into biodiesel using a lipase (Eversa Transform 2.0 Novozymes) as the catalyst and ethanol as the alcohol. The optimization of reaction yields was carried out using a factorial design (FD) and response surface methodology (RSM). The obtained models were used to determine the optimum operating conditions for an upscaling scenario, and provided a thorough understanding of the reaction mechanism. The factorial design was developed with the varying temperature (between 30 and 40 °C) and amount of catalysts (between 5 and 9 wt%), while the alcohol/oil molar ratio was kept constant at 6 : 1. It was found that the highest achievable yields, within the range of operating conditions tested, were reached when the catalyst concentration was 4.2%, the alcohol/oil molar ratio was 6 : 1 and the operation temperature was 36 °C with model R 2 = 91.77 for the linear model. Within these operating conditions, the yield of FAEE was above 98%. The FAEE produced can be used as a promising substitute for petroleum-based diesel fuels, since it fulfills the European Biodiesel Standard EN 14214 in all aspects tested except for the oxidation time.